Peningkatan Keterampilan Motorik Kasar melalui Permainan Lompat Tali pada Siswa Kelompok B TK Pertiwi 1 Pengkol, Sragen - Suratmi, Suratmi (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Gross motor skills are an important aspect for the development and growth of children. Based on the background above, the formulation of the problem in this study was